New Bioinsecticides From Combination Extract of Leaf and Flower of Breadfruit (Artocarpus Altilis) On Mortality of Aedes Aegypti Larvae - Rahma Nindiastuti; Dwi Wahyuni; Isa Ma’rufi (Jurnal Health Sains, 2022)
The main vector for the spread of dengue fever is the female mosquito Aedes aegypti. In Indonesia, chemical larvicides are commonly used to control Aedes aegypti larvae. Bioinsecticides made from plants are one option for environmentally friendly larvae control. Leaves and flower of breadfruit Artocarpus altilis contains toxic compound that can function as larvicides. This experimental study used combination of leaf and flower of breadfruit expect that the combination of the two extracs was synergistic and it was more effective in killing Aedes aegypti larvae. The third instar Aedes aegypti larvae was used and divided into control group and test group with concentrations 1000, 2750, 4500, and 6250 ppm and replicated in 3 times with observations every 6, 9, and 24 hours. To identify the significant difference, the mortality data was analyzed using ANOVA and Duncan's test. In probit analysis, LC50 value of breadfruit leaf extract was 1871 ppm with LT50 was 4.2 hours. LC50 value of breadfruit flower extract was 2531 ppm with LT50 was 10.8 hours. LC50 value of the combination of breadfruit leaf and flower extract was 903 ppm with LT50 was 3.7 hours. Based on these studies, it may be indicated that breadfruit leaves and flowers was more effective in killing Aedes aegypti larvae than single extracts